Preparation process of high-adhesion anti-cracking liquid metal film

By using a combination process of polyurethane adhesive, mixed liquid silicone rubber and liquid metal, the problem of liquid metal films being prone to cracking and insufficient adhesion is solved, and a liquid metal film with high adhesion and crack resistance is achieved, which is suitable for the field of fine electronic manufacturing.

CN119505306APending Publication Date: 2025-02-25CHONGQING VOCATIONAL INST OF ENG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411575804.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional liquid metal films have problems such as prone to cracking and insufficient adhesion, which limits their application prospects in the field of fine electronic manufacturing.

Method used

A combination of polyurethane adhesive, mixed liquid silicone rubber and liquid metal is used to make a high adhesion and cracking resistance liquid metal film by uniform mixing and applying on the substrate.

Benefits of technology

It improves the adhesion and crack resistance of liquid metal films, enhances its stability under high temperature and tensile conditions, and is suitable for the field of fine electronic manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505306A_ABST
    Figure CN119505306A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of a high-adhesion anti-cracking liquid metal film, and relates to the technical field of metal materials. The high-adhesion anti-cracking liquid metal film is prepared from the following components in parts by mass: 30 to 60 parts of polyurethane adhesive, 20 to 50 parts of mixed liquid silicone rubber and 10 to 20 parts of liquid metal. The polyurethane adhesive contains ester bonds and ether bonds, the mixed liquid silicone rubber contains a tackifier, and modified siloxane is added into the tackifier. According to the invention, ester bonds and ether bonds are introduced in the synthesis process of polyester polyol, so that the product has the characteristics of polyester and polyether, and the toughness and weather resistance of the polyurethane adhesive are improved; the tackifier is added into the liquid silicone rubber, so that the adhesive property of the liquid silicone rubber is enhanced, the compatibility of the liquid silicone rubber and polyurethane is improved by adding the modified siloxane, so that the liquid silicone rubber can be better combined with polyurethane, and the prepared film has better tensile property and adhesive property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal materials, in particular to a preparation process of a high-adhesion and crack-resistant liquid metal film. Background Art

[0002] Liquid metal films have been widely studied and applied in recent years due to their excellent conductive properties and flexibility. However, traditional liquid metal films have problems such as easy cracking and insufficient adhesion, which limits their application prospects in the field of precision electronic manufacturing.

[0003] Chinese patent CN116959782A discloses a flexible liquid metal film, its preparation method and application. Liquid metal is used as the conductive material and is mechanically blended with a silicone rubber elastomer to obtain the liquid metal film. The film has a simple preparation process and good flexibility. It has good application prospects in the fields of electromagnetic shielding and stretchable conductors.

[0004] However, the viscosity of silicone rubber elastomer is low, and the prepared film is easy to fall off from the substrate, which has a great impact on the integrity and function of the circuit. Therefore, we propose a preparation process for high-adhesion and crack-resistant liquid metal film. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation process of a high-adhesion and crack-resistant liquid metal film to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solution: a high-adhesion and crack-resistant liquid metal film, comprising the following components by mass: 30 to 60 parts of polyurethane adhesive, 20 to 50 parts of mixed liquid silicone rubber, and 10 to 20 parts of liquid metal.

[0007] A preparation process of a high-adhesion and crack-resistant liquid metal film, comprising the following processes:

[0008] The polyurethane adhesive, the mixed liquid silicone rubber and the liquid metal are evenly mixed to obtain a mixed liquid, and the mixed liquid is applied on a substrate and cured to obtain a liquid metal film.

[0009] Furthermore, the curing process conditions are: temperature 20-80° C., time 1-3 h.

[0010] Furthermore, the thickness of the liquid metal film is 50 to 200 μm.

[0011] Furthermore, the liquid metal is a gallium-indium alloy, a gallium-indium-tin alloy, or a mixture of the two.

[0012] Further, the polyurethane adhesive is prepared by the following process:

[0013] The polyether ester polyol, diphenylmethane diisocyanate and antioxidant are mixed, stirred evenly, heated to react under the protection of nitrogen atmosphere, cooled after the reaction, and a chain extender is added, reacted for 6 to 10 minutes to obtain a polyurethane adhesive.

[0014] Furthermore, the mass ratio of polyether ester polyol, diphenylmethane diisocyanate, antioxidant and chain extender is (4-6): (1-2): (0.5-1): (0.3-0.5).

[0015] Furthermore, the process conditions of the heating reaction are: temperature 60-70°C, time 1-2h;

[0016] Cool down to 50-60℃.

[0017] Further, diphenylmethane diisocyanate: CAS number is 101-68-8, from Yinglang Chemical;

[0018] The antioxidant is 2246, CAS No. 119-47-1, from Changzhou Xince Polymer Materials Co., Ltd.

[0019] The chain extender is 1,4-butanediol, CAS No. 110-63-4, purity 99.5%, sourced from Nanjing Baojiarui Chemical Co., Ltd.

[0020] Further, the polyetherester polyol is prepared by the following process:

[0021] Adipic acid, butanediol, polytetrahydrofuran ether diol and a catalyst are mixed, and heated to react under the protection of a nitrogen atmosphere. When the acid value of the system is 10-20 mg / KOH, tetrabutyl titanate is added, and the mixture is stirred evenly. The temperature is increased and vacuum is applied. When the acid value of the system is 0.3-0.36 mg / KOH and the hydroxyl value is 57-57.4 mg / KOH, vacuum application is stopped, the temperature is lowered, and the mixture is collected to obtain a polyether ester polyol.

[0022] Furthermore, the mass ratio of adipic acid, polytetramethylene glycol, butanediol, catalyst and tetrabutyl titanate is (0.6-1):(1-1.2):(0.3-0.5):(0.2-0.4):(0.05-0.1).

[0023] Further, the process conditions of the heating reaction are: temperature 130-180°C;

[0024] Raise the temperature to 220-230°C and then cool down to 100-120°C.

[0025] Further, adipic acid: CAS number 124-04-9, purity 99%, sourced from Nanjing Shengqinghe Chemical Co., Ltd.;

[0026] Polytetramethylene glycol: CAS number is 25190-06-1, from Merck reagent;

[0027] Butanediol: CAS number is 110-63-4, purity is 99%, from Jinan Linsheng Chemical Co., Ltd.

[0028] The catalyst is dodecyltrimethoxysilane, CAS No. 3069-21-4, purity 99%, sourced from Shandong Yuanjin New Materials Co., Ltd.;

[0029] Tetrabutyl titanate: CAS number is 5593-70-4, sourced from Shandong Dongfang Riqi New Materials Co., Ltd.

[0030] In the above technical scheme, the synthesis route of polyester is adopted, and polyether polyol is introduced in the synthesis process of polyester polyol. The active terminal hydroxyl group of polyester polyol and the terminal carboxyl group in adipic acid are used for alkyd condensation reaction, and the obtained polyether ester polyol contains both ester bond segments and ether bond segments. The ester bond has the characteristics of high cohesive energy and large polarity, which can give the material good wear resistance and high strength, but poor low temperature resistance and hydrolysis resistance; the ether bond has low cohesive energy and high segment flexibility, and the product containing ether bond has the advantages of high toughness, low temperature resistance and hydrolysis resistance; the combination of the two, the obtained polyether ester polyol has the characteristics of polyester and polyether, and effectively improves the toughness, low temperature resistance and wear resistance of polyurethane adhesive. The addition of antioxidant 2246 can delay the aging process of polyurethane adhesive under high temperature, ultraviolet radiation and chemical oxidation, and further improve the durability and stability of polyurethane adhesive.

[0031] Further, the mixed liquid silicone rubber is prepared by the following process:

[0032] The mixed liquid silicone rubber and the tackifier are mixed and vacuum degassed to obtain the mixed liquid silicone rubber.

[0033] Furthermore, the mass ratio of the mixed liquid silicone rubber and the tackifier is (2-3): (1-3).

[0034] Furthermore, the vacuum degassing time is 30 to 40 minutes.

[0035] Furthermore, the mixed liquid silicone rubber is 107 rubber with a purity of 99%, which is sourced from Jinan Yingyu Chemical Co., Ltd.

[0036] Further, the tackifier is prepared by the following process:

[0037] S1: preheat the mixture of methylphenyldimethoxysilane and deionized water to 60-70°C, add an acidic cation exchange resin, react for 1-2h, remove the acidic cation exchange resin by vacuum filtration to obtain a filtrate, and vacuum distill the filtrate to obtain methylphenyl terminal hydroxyl silicone oil;

[0038] S2: preheat the mixture of methylphenyl terminal hydroxyl silicone oil, methylvinyl dimethoxysilane and modified siloxane to 85-95°C, add alkaline anion exchange resin, react for 3-4 hours, remove the alkaline anion exchange resin by vacuum filtration to obtain a filtrate, and distill the filtrate under reduced pressure to obtain a thickener.

[0039] Furthermore, in S1, the mass ratio of methylphenyldimethoxysilane, deionized water, and acidic cation exchange resin is (3-5): (2-4): (0.05-0.1).

[0040] Furthermore, in S1, the process conditions of reduced pressure distillation are: temperature 70 to 80°C, pressure -0.1 to -0.096 MPa.

[0041] Further, in S1, methylphenyldimethoxysilane: CAS number is 3027-21-2, purity is 99%, and is sourced from Anhui Mingyi Silicon Industry Co., Ltd.;

[0042] Acidic cation exchange resin, particle size 0.315 ~ 1.25mm, comes from Langfang Jinnan Resin Co., Ltd.

[0043] Furthermore, in S2, the molar ratio of methylphenyl terminal hydroxyl silicone oil, methylvinyl dimethoxysilane, modified siloxane, and basic anion exchange resin is (0.5-1): (0.1-0.5): (0.5-1): (0.05-0.1).

[0044] Furthermore, in S2, the process conditions of reduced pressure distillation are: temperature 100 to 120°C, pressure -0.1 to -0.096 MPa.

[0045] Further, methylvinyldimethoxysilane: CAS number 16753-62-1, purity 97%, sourced from Shanghai Yuanye Biotechnology Co., Ltd.;

[0046] Alkaline anion exchange resin: particle size 0.315~1.25mm, sourced from Langfang Jinnan Resin Co., Ltd.

[0047] Further, the modified siloxane described in S2 is prepared by the following process:

[0048] Step (1): dissolving biphenyl diether dianhydride in acetone, heating to 45-55° C. under nitrogen atmosphere, adding phenylacetylene, reflux for 4-6 hours, adding acetic anhydride and triethylamine in sequence, heating to react, rotary evaporation after the reaction, washing, repeating 3-5 times for recrystallization to obtain an intermediate;

[0049] Step (2): Under the protection of nitrogen atmosphere, the intermediate and acetone are mixed evenly, 3-methacryloxypropylmethyldimethoxysilane is added dropwise, and heated to react to obtain modified siloxane.

[0050] Furthermore, in step (1), the molar ratio of biphenyl diether dianhydride, acetone, phenylacetylene, acetic anhydride and triethylamine is 1:(10-18):(10-18):(1-2.5):(1-3).

[0051] Furthermore, the process conditions of the temperature-raising reaction in step (1) are: temperature 70-80° C., time 2-4 h;

[0052] The process conditions of rotary evaporation are: temperature 30-40°C, time 1-2h.

[0053] Furthermore, in step (2), the dropping speed is 1 to 3 s / drop.

[0054] Furthermore, in step (1), biphenyl diether dianhydride: CAS No. 26177-82-2, purity 99%, sourced from Hubei Dali Chemical Co., Ltd.;

[0055] Acetone: CAS number is 67-64-1, purity is 99%, from Suzhou Qianan Chemical Raw Materials Co., Ltd.

[0056] Phenylacetylene: CAS number is 536-74-3, purity is 99%, from Shandong Xiaoqing New Chemical Co., Ltd.;

[0057] Acetic anhydride: CAS number is 108-24-7, purity is 98.5%, sourced from Guangdong Xiaoda Chemical Co., Ltd.;

[0058] Triethylamine: CAS number is 121-44-8, purity is 99%, sourced from Jinan Qihang Chemical Technology Co., Ltd.

[0059] 3-Methacryloyloxypropylmethyldimethoxysilane, CAS No. 14513-34-9, purity 98%, sourced from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.

[0060] Furthermore, in step (2), the mass ratio of the intermediate, acetone, and 3-methacryloxypropylmethyldimethoxysilane is 1:(5-10):1.

[0061] Furthermore, in step (2), the process conditions for the heating reaction are: temperature 45-55° C., time 4-6 h.

[0062] In the above technical solution, most of the side chains of the silicone rubber molecular chain are non-polar groups, which are difficult to bond with other materials. The present invention obtains methylphenyl terminal hydroxyl silicone oil by hydrolysis and condensation, and then uses a non-hydrolytic sol-gel method to obtain a tackifier through polycondensation reaction to improve its bonding strength. However, the direct blending method may cause problems such as decreased stability of the mixed liquid silicone rubber and decreased viscosity of the tackifier. Therefore, modified siloxane is added to the tackifier to improve the compatibility between the two. The acryloxy group in siloxane contains a carbon-carbon double bond and has high reactivity. The siloxane is modified so that the acryloxy group forms a stable chemical bond with the ether bond and the imide ring. The crosslinking strength between the siloxane, the thickener and the mixed liquid silicone rubber is enhanced through the action of the chemical bond, and the bonding performance between the thickener and the liquid silicone rubber is improved; the imide ring has good thermal stability and strong polarity, which can enhance the crosslinking strength between the siloxane, the thickener and the mixed liquid silicone rubber, and to a certain extent enhance the heat resistance of the mixed liquid silicone rubber. The ether bond is a flexible molecular chain, which enhances the toughness of the mixed liquid silicone rubber and further enhances the tensile strength of the metal film.

[0063] Compared with the prior art, the present invention has the following beneficial effects:

[0064] 1. By introducing polyether polyols into the synthesis process of polyester polyols, a polyether ester polyol containing both ester bond segments and ether bond segments is obtained. The cohesive energy of ester bonds is high and the polarity is large, so that the obtained polyurethane has strong wear resistance and high strength, but poor low temperature resistance and hydrolysis resistance. Ether bonds have the advantages of high toughness, low temperature resistance and hydrolysis resistance. Combining the two, the obtained polyether ester polyol has the characteristics of both polyester and polyether, which effectively improves the toughness, low temperature resistance and wear resistance of polyurethane adhesives.

[0065] 2. Most of the side chains of silicone rubber molecular chains are non-polar groups, which are difficult to bond with other materials. The present invention obtains methylphenyl terminal hydroxyl silicone oil by hydrolysis condensation, and then uses a non-hydrolytic sol-gel method to obtain a tackifier through a condensation reaction to improve its bonding strength. However, the direct blending method may lead to problems such as decreased stability of the mixed liquid silicone rubber and decreased viscosity of the tackifier. The siloxane in the tackifier is modified so that the acryloxy group forms a stable chemical bond with the ether bond and the imide ring. The crosslinking strength between the siloxane, the tackifier and the mixed liquid silicone rubber is enhanced through the action of the chemical bond, thereby improving the bonding performance of the tackifier and the liquid silicone rubber. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 This is a schematic diagram of the liquid metal film obtained in Comparative Example 3 of the present invention after being pressed by a finger;

[0067] Figure 2 This is a schematic diagram of the liquid metal film obtained in Example 3 of the present invention after being pressed by a finger;

[0068] Figure 3 This is a schematic diagram of a tensile test of the liquid metal film obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0069] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0070] In the following specific embodiments,

[0071] The liquid metal is gallium-indium alloy, grade: GI99.99, purity 99.9%, from Changsha Kunyong New Materials Co., Ltd.

[0072] Diphenylmethane diisocyanate: CAS number is 101-68-8, from Yinglang Chemical;

[0073] The antioxidant is 2246, CAS No. 119-47-1, from Changzhou Xince Polymer Materials Co., Ltd.

[0074] The chain extender is 1,4-butanediol, CAS No. 110-63-4, purity 99.5%, sourced from Nanjing Baojiarui Chemical Co., Ltd.;

[0075] Adipic acid: CAS number is 124-04-9, purity is 99%, from Nanjing Shengqinghe Chemical Co., Ltd.

[0076] Polytetramethylene glycol: CAS number is 25190-06-1, from Merck reagent;

[0077] Butanediol: CAS number is 110-63-4, purity is 99%, from Jinan Linsheng Chemical Co., Ltd.

[0078] The catalyst is dodecyltrimethoxysilane, CAS No. 3069-21-4, purity 99%, sourced from Shandong Yuanjin New Materials Co., Ltd.;

[0079] Tetrabutyl titanate: CAS number is 5593-70-4, from Shandong Dongfang Riqi New Materials Co., Ltd.

[0080] The mixed liquid silicone rubber is 107 rubber with a purity of 99%, which comes from Jinan Yingyu Chemical Co., Ltd.

[0081] Methylphenyldimethoxysilane: CAS number is 3027-21-2, purity is 99%, from Anhui Mingyi Silicon Industry Co., Ltd.

[0082] Acidic cation exchange resin, particle size 0.315-1.25 mm, sourced from Langfang Jinnan Resin Co., Ltd.;

[0083] Methylvinyldimethoxysilane: CAS number is 16753-62-1, purity is 97%, from Shanghai Yuanye Biotechnology Co., Ltd.

[0084] Basic anion exchange resin: particle size 0.315-1.25 mm, sourced from Langfang Jinnan Resin Co., Ltd.

[0085] Biphenyl diether dianhydride: CAS number is 26177-82-2, purity is 99%, from Hubei Dali Chemical Co., Ltd.

[0086] Acetone: CAS number is 67-64-1, purity is 99%, from Suzhou Qianan Chemical Raw Materials Co., Ltd.

[0087] Phenylacetylene: CAS number is 536-74-3, purity is 99%, from Shandong Xiaoqing New Chemical Co., Ltd.;

[0088] Acetic anhydride: CAS number is 108-24-7, purity is 98.5%, sourced from Guangdong Xiaoda Chemical Co., Ltd.;

[0089] Triethylamine: CAS number is 121-44-8, purity is 99%, sourced from Jinan Qihang Chemical Technology Co., Ltd.

[0090] 3-Methacryloxypropylmethyldimethoxysilane, CAS No. 14513-34-9, purity 98%, from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.;

[0091] Commercially available polyurethane adhesive: CAS number 57834-33-0, purity 98%, sourced from Nanjing Milan New Materials Co., Ltd.

[0092] Embodiment 1: A process for preparing a high-adhesion and crack-resistant liquid metal film, comprising the following processes:

[0093] (1) Preparation of polyurethane adhesive:

[0094] Adipic acid, butanediol, polytetrahydrofuran ether diol and a catalyst are mixed, heated to 130°C for reaction under the protection of nitrogen atmosphere, and tetrabutyl titanate is added when the acid value of the system is 10 mg / KOH, stirred evenly, heated to 220°C, and vacuumed. When the acid value of the system is 0.3 mg / KOH and the hydroxyl value is 57 mg / KOH, vacuuming is stopped, the temperature is lowered to 100°C, and the mixture is collected to obtain polyether ester polyol; the mass ratio of adipic acid, polytetrahydrofuran ether diol, butanediol, catalyst and tetrabutyl titanate is 0.6:1:0.3:0.2:0.05;

[0095] The polyether ester polyol, diphenylmethane diisocyanate and antioxidant were mixed and stirred evenly, and heated to 60°C for reaction for 1 hour under the protection of nitrogen atmosphere. After the reaction, the temperature was lowered to 50°C, and a chain extender was added and reacted for 6 minutes to obtain a polyurethane adhesive; the mass ratio of the polyether ester polyol, diphenylmethane diisocyanate, antioxidant and chain extender was 4:1:0.5:0.3;

[0096] (2) Preparation of mixed liquid silicone rubber:

[0097] ① Dissolve biphenyl diether dianhydride in acetone, heat to 45°C under nitrogen atmosphere, add phenylacetylene, reflux for 4h, add acetic anhydride and triethylamine in sequence, heat to react, and after the reaction, perform rotary evaporation, wash, repeat 3 times for recrystallization to obtain an intermediate; ② Under nitrogen atmosphere, mix the intermediate and acetone evenly, add siloxane at a rate of 1s / drop, heat to react, and obtain modified siloxane; ① The molar ratio of biphenyl diether dianhydride, acetone, phenylacetylene, acetic anhydride, and triethylamine is 1:10:10:1:1; the process conditions for the temperature reaction are: temperature 70°C, time 2h; the process conditions for the rotary evaporation are: temperature 30°C, time 1h; ② The mass ratio of the intermediate, acetone, and siloxane is 1:5:1; the process conditions for the heating reaction are: temperature 45°C, time 4h;

[0098] S1: preheat the mixture of methylphenyldimethoxysilane and deionized water to 60°C, add acidic cation exchange resin, react for 1 hour, remove the acidic cation exchange resin by vacuum filtration to obtain a filtrate, and vacuum distill the filtrate to obtain methylphenyl terminal hydroxyl silicone oil; the mass ratio of methylphenyldimethoxysilane, deionized water, and acidic cation exchange resin is 3:2:0.05; the process conditions of vacuum distillation are: temperature 70°C, pressure -0.1MPa; S2: , methylvinyl dimethoxysilane, and modified siloxane are mixed and preheated to 85°C, basic anion exchange resin is added, and the reaction is carried out for 3 hours. The basic anion exchange resin is removed by vacuum filtration to obtain a filtrate, and the filtrate is vacuum distilled to obtain a tackifier; the molar ratio of methylphenyl terminal hydroxyl silicone oil, methylvinyl dimethoxysilane, modified siloxane, and basic anion exchange resin is 0.5:0.1:0.5:0.05; the process conditions of vacuum distillation are: temperature 100°C, pressure -0.1MPa;

[0099] The liquid silicone rubber and the tackifier are mixed in a mass ratio of 2:1, and vacuum degassing is performed to obtain a mixed liquid silicone rubber; the vacuum degassing time is 30 minutes;

[0100] (3) Preparation of liquid metal film:

[0101] The polyurethane adhesive, mixed liquid silicone rubber and liquid metal are evenly mixed in a mass ratio of 3:2:1 to obtain a mixed liquid, and the mixed liquid is applied to a substrate and heated and cured to obtain a liquid metal film; the process conditions for heating and curing are: temperature 20°C, time 1h; the thickness of the liquid metal film is 50μm.

[0102] Embodiment 2: A preparation process of a high-adhesion and crack-resistant liquid metal film, comprising the following processes:

[0103] (1) Preparation of polyurethane adhesive:

[0104] Adipic acid, butanediol, polytetrahydrofuran ether diol and a catalyst are mixed, heated to 155°C for reaction under the protection of nitrogen atmosphere, tetrabutyl titanate is added when the acid value of the system is 15 mg / KOH, stirred evenly, heated to 225°C, and vacuumed, and when the acid value of the system is 0.33 mg / KOH and the hydroxyl value is 57.2 mg / KOH, vacuuming is stopped, the temperature is lowered to 110°C, and the polyether ester polyol is obtained; the mass ratio of adipic acid, polytetrahydrofuran ether diol, butanediol, catalyst and tetrabutyl titanate is 0.8:1.1:0.4:0.3:0.07;

[0105] The polyether ester polyol, diphenylmethane diisocyanate and antioxidant were mixed and stirred evenly, and heated to 65°C for reaction for 1.5 hours under nitrogen atmosphere protection. After the reaction, the temperature was lowered to 55°C, and a chain extender was added and reacted for 8 minutes to obtain a polyurethane adhesive; the mass ratio of the polyether ester polyol, diphenylmethane diisocyanate, antioxidant and chain extender was 5:1.5:0.7:0.4;

[0106] (2) Preparation of mixed liquid silicone rubber:

[0107] ① Dissolve biphenyl diether dianhydride in acetone, heat to 50°C under nitrogen atmosphere, add phenylacetylene, reflux for 5h, add acetic anhydride and triethylamine in sequence, heat to react, and after the reaction, perform rotary evaporation, wash, repeat 4 times for recrystallization to obtain an intermediate; ② Under nitrogen atmosphere, mix the intermediate and acetone evenly, add siloxane at a rate of 2s / drop, heat to react, and obtain modified siloxane; ① The molar ratio of biphenyl diether dianhydride, acetone, phenylacetylene, acetic anhydride, and triethylamine is 1:14:14:2:2; the process conditions for temperature reaction are: temperature 75°C, time 3h; the process conditions for rotary evaporation are: temperature 35°C, time 1.5h; ② The mass ratio of intermediate, acetone, and siloxane is 1:7:1; the process conditions for heating reaction are: temperature 50°C, time 5h;

[0108] S1: preheat the mixture of methylphenyldimethoxysilane and deionized water to 65°C, add acidic cation exchange resin, react for 1.5h, remove the acidic cation exchange resin by vacuum filtration to obtain a filtrate, and vacuum distill the filtrate to obtain methylphenyl terminal hydroxyl silicone oil; the mass ratio of methylphenyldimethoxysilane, deionized water, and acidic cation exchange resin is 4:3:0.07; the process conditions of vacuum distillation are: temperature 75°C, pressure -0.098MPa; S2: , methylvinyl dimethoxysilane, and modified siloxane are mixed and preheated to 90°C, basic anion exchange resin is added, and the reaction is carried out for 3.5 hours. The basic anion exchange resin is removed by vacuum filtration to obtain a filtrate, and the filtrate is vacuum distilled to obtain a tackifier; the molar ratio of methylphenyl terminal hydroxyl silicone oil, methylvinyl dimethoxysilane, modified siloxane, and basic anion exchange resin is 0.7:0.3:0.3:0.07; the process conditions of vacuum distillation are: temperature 110°C, pressure -0.098MPa;

[0109] The liquid silicone rubber and the tackifier were mixed in a mass ratio of 4:2, and vacuum degassing was performed to obtain a mixed liquid silicone rubber; the vacuum degassing time was 35 minutes;

[0110] (3) Preparation of liquid metal film:

[0111] The polyurethane adhesive, mixed liquid silicone rubber and liquid metal are evenly mixed in a mass ratio of 5:3:1.5 to obtain a mixed liquid, and the mixed liquid is applied to a substrate and heated and cured to obtain a liquid metal film; the process conditions for heating and curing are: temperature 50°C, time 2h; the thickness of the liquid metal film is 100μm.

[0112] Embodiment 3: A process for preparing a high-adhesion and crack-resistant liquid metal film, comprising the following processes:

[0113] (1) Preparation of polyurethane adhesive:

[0114] Adipic acid, butanediol, polytetrahydrofuran ether diol and a catalyst are mixed, heated to 180°C for reaction under the protection of nitrogen atmosphere, and tetrabutyl titanate is added when the acid value of the system is 20 mg / KOH, stirred evenly, heated to 230°C, and vacuumed. When the acid value of the system is 0.36 mg / KOH and the hydroxyl value is 57.4 mg / KOH, vacuuming is stopped, the temperature is lowered to 120°C, and the polyether ester polyol is obtained; the mass ratio of adipic acid, polytetrahydrofuran ether diol, butanediol, catalyst and tetrabutyl titanate is 1:1.2:0.5:0.4:0.1;

[0115] The polyether ester polyol, diphenylmethane diisocyanate and antioxidant were mixed and stirred evenly, and heated to 70°C for reaction for 2 hours under nitrogen atmosphere protection. After the reaction, the temperature was lowered to 60°C, and a chain extender was added and reacted for 10 minutes to obtain a polyurethane adhesive; the mass ratio of the polyether ester polyol, diphenylmethane diisocyanate, antioxidant and chain extender was 6:2:1:0.5;

[0116] (2) Preparation of mixed liquid silicone rubber:

[0117] ① Dissolve biphenyl diether dianhydride in acetone, heat to 55°C under nitrogen atmosphere, add phenylacetylene, reflux for 6h, add acetic anhydride and triethylamine in sequence, heat to react, and after the reaction, perform rotary evaporation, wash, repeat 5 times for recrystallization to obtain an intermediate; ② Under nitrogen atmosphere, mix the intermediate and acetone evenly, add siloxane at a rate of 3s / drop, heat to react, and obtain modified siloxane; ① The molar ratio of biphenyl diether dianhydride, acetone, phenylacetylene, acetic anhydride, and triethylamine is 1:18:18:2.5:3; the process conditions for the temperature reaction are: temperature 80°C, time 4h; the process conditions for the rotary evaporation are: temperature 40°C, time 2h; ② The mass ratio of the intermediate, acetone, and siloxane is 1:10:1; the process conditions for the heating reaction are: temperature 55°C, time 6h;

[0118] S1: preheat the mixture of methylphenyldimethoxysilane and deionized water to 70°C, add acidic cation exchange resin, react for 2h, remove the acidic cation exchange resin by vacuum filtration to obtain a filtrate, and vacuum distill the filtrate to obtain methylphenyl terminal hydroxyl silicone oil; the mass ratio of methylphenyldimethoxysilane, deionized water, and acidic cation exchange resin is 5:4:0.1; the process conditions of vacuum distillation are: temperature 80°C, pressure -0.1MPa; S2: preheat the mixture of methylphenyl terminal hydroxyl silicone oil, methylvinyldimethoxysilane, and modified siloxane to 95°C, add basic anion exchange resin, react for 4h, remove the basic anion exchange resin by vacuum filtration to obtain a filtrate, and vacuum distill the filtrate to obtain a tackifier; the molar ratio of methylphenyl terminal hydroxyl silicone oil, methylvinyldimethoxysilane, modified siloxane, and basic anion exchange resin is 1:0.5:1:0.1; the process conditions of vacuum distillation are: temperature 120°C, pressure -0.1MPa;

[0119] The liquid silicone rubber and the tackifier are mixed in a mass ratio of 3:3, and vacuum degassing is performed to obtain a mixed liquid silicone rubber; the vacuum degassing time is 40 minutes;

[0120] (3) Preparation of liquid metal film:

[0121] The polyurethane adhesive, mixed liquid silicone rubber and liquid metal are evenly mixed in a mass ratio of 6:5:2 to obtain a mixed liquid, and the mixed liquid is applied to a substrate and heated and cured to obtain a liquid metal film; the process conditions for heating and curing are: temperature 80°C, time 3h; the thickness of the liquid metal film is 200μm.

[0122] Comparative Example 1: Taking Example 1 as an example, the polyurethane adhesive was replaced with a commercially available polyurethane adhesive, and the other conditions remained unchanged.

[0123] Comparative Example 2: Taking Example 1 as an example, no modified siloxane is added to the tackifier, and other conditions remain unchanged.

[0124] Comparative Example 3: Taking Example 1 as an example, no tackifier is added to the liquid silicone rubber, and other conditions remain unchanged.

[0125] experiment:

[0126] The liquid metal films obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were prepared into samples, and their performance was tested at -70°C, 25°C, and 180°C respectively:

[0127] Viscosity test: The liquid metal film was tested using a ROTAVISC ME-VI rotational viscometer with a rotor speed of 10 r / min.

[0128] Mechanical properties test: UTM6502 tensile testing machine was used to conduct elongation at break test and tensile test, with a tensile rate of 2 mm / min;

[0129] Adhesion test: Based on GB / T 1732-1993, the adhesion of liquid metal film to substrate is tested.

[0130]

[0131] Table 1 - Performance test results at 70℃

[0132]

[0133] Table 2 Performance test results at 25℃

[0134]

[0135] Table 3 Performance test results at 180℃

[0136] According to the data in the above table, we can clearly draw the following conclusions:

[0137] The liquid metal films obtained in Examples 1 to 3 are compared with the liquid metal films obtained in Comparative Examples 1 to 3. The test results show that:

[0138] Compared with Example 1, the polyurethane adhesive in Comparative Example 1 is replaced with a commercially available polyurethane adhesive, and its viscosity and adhesion are significantly reduced. The reason is that the main components of the commercially available polyurethane adhesive are polyols and polyurethane, which have low viscosity; the viscosity, elongation at break, tensile strength and adhesion of Comparative Example 2 are reduced because no modified siloxane is added to the tackifier, and the reason is that the direct blending of liquid silicone rubber and tackifier may cause poor compatibility between the two, resulting in a decrease in the viscosity of the tackifier and a decrease in the mechanical properties of the polyurethane; Comparative Example 3 does not add a tackifier to the liquid silicone rubber, and the viscosity, elongation at break, tensile strength and adhesion are greatly reduced. The reason is that the viscosity of the single liquid silicone rubber component is poor, and the interaction force between the non-polar groups of its molecular side chains and the polyurethane adhesive is low, resulting in a decrease in various mechanical properties and viscosity. It can be seen that the preparation process of the liquid metal film and the setting of the components used in the present application can promote the comprehensive improvement of its viscosity, elongation at break and tensile strength.

[0139] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A process for preparing a high-adhesion and crack-resistant liquid metal film, characterized in that: The following steps are involved: The polyurethane adhesive, the mixed liquid silicone rubber and the liquid metal are evenly mixed to obtain a mixed liquid, and the mixed liquid is applied on a substrate and cured to obtain a liquid metal film.

2. The process for preparing a highly adhesive and crack-resistant liquid metal film according to claim 1, characterized in that: The mixed liquid silicone rubber is obtained by mixing liquid silicone rubber and a tackifier, and the tackifier is prepared by the following process: S1: preheat the mixture of methylphenyldimethoxysilane and deionized water to 60-70°C, add an acidic cation exchange resin, and react for 1-2 hours to obtain methylphenyl terminal hydroxyl silicone oil; S2: preheat methylphenyl terminal hydroxyl silicone oil, methylvinyl dimethoxysilane, and modified siloxane to 85-95° C., add alkaline anion exchange resin, and react for 3-4 hours to obtain a tackifier.

3. The process for preparing a highly adhesive and crack-resistant liquid metal film according to claim 2, characterized in that: The modified siloxane is prepared by the following process: Step (1): dissolving biphenyl diether dianhydride in acetone, heating to 45-55° C. under nitrogen atmosphere, adding phenylacetylene, reflux for 4-6 hours, adding acetic anhydride and triethylamine in sequence, and reacting at elevated temperature to obtain an intermediate; Step (2): Under the protection of nitrogen atmosphere, the intermediate and acetone are mixed evenly, 3-methacryloxypropylmethyldimethoxysilane is added dropwise, and heated to react to obtain modified siloxane.

4. The process for preparing a highly adhesive and crack-resistant liquid metal film according to claim 1, characterized in that: The polyurethane adhesive is prepared by the following process: The polyether ester polyol, diphenylmethane diisocyanate and antioxidant are mixed, stirred evenly, heated to react under the protection of nitrogen atmosphere, cooled after the reaction, and a chain extender is added, reacted for 6 to 10 minutes to obtain a polyurethane adhesive.

5. The process for preparing a highly adhesive and crack-resistant liquid metal film according to claim 4, characterized in that: The polyether ester polyol is prepared by the following process: Adipic acid, butanediol, polytetrahydrofuran ether diol and a catalyst are mixed, and heated to react under the protection of a nitrogen atmosphere. When the acid value of the system is 10-20 mg / KOH, tetrabutyl titanate is added, and the mixture is stirred evenly. The temperature is increased and vacuum is applied. When the acid value of the system is 0.3-0.36 mg / KOH and the hydroxyl value is 57-57.4 mg / KOH, vacuum application is stopped, the temperature is lowered, and the mixture is collected to obtain a polyether ester polyol.

6. The process for preparing a highly adherent and crack-resistant liquid metal film according to claim 1, characterized in that: The mass ratio of polyurethane adhesive, mixed liquid silicone rubber and liquid metal is (3-6):(2-5):(1-2).

7. The process for preparing a highly adherent and crack-resistant liquid metal film according to claim 2, characterized in that: The process conditions of the reduced pressure distillation in S1 are: temperature 70 to 80°C, pressure -0.1 to -0.096 MPa.

8. The process for preparing a highly adherent and crack-resistant liquid metal film according to claim 2, characterized in that: The process conditions of the reduced pressure distillation in S2 are: temperature 100-120°C, pressure -0.1-0.096MPa.

9. The process for preparing a highly adhesive and crack-resistant liquid metal film according to claim 3, characterized in that: In step (1), the molar ratio of biphenyl diether dianhydride, acetone, phenylacetylene, acetic anhydride and triethylamine is 1:(10-18):(10-18):(1-2.5):(1-3).

10. A high-adhesion and crack-resistant liquid metal film, characterized in that: The invention is prepared by the preparation process described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flexible liquid metal film and preparation method and application thereof

    CN116959782A